ENT 600 : TIKON pillow / Nur Atikah Izamri … [et al.] - Zamri, Nur Atikah; Hairul Azhar, Nur Maizatul Maizan; Hamran, Nur Amira Syahira; Zanuddin, Siti Farah Eliza (2016)
After having through some process of searching and reviewing the issues toward the problem suffered by people whom diagnosed with insomnia problem or sickness, some observation were later being conducted in order to ponder more on the symptoms and sign of the sickness and also some observation on an alternative way to help those people. The team had agreed to come out with a product that we believe can contribute to aid the insomnia patient for a better days ahead. Our product is called as TIKON Pillow.